The Influence of CSR Implementation, Hospital Image, and Patient Trust on Interest in Seeking Treatment - Nadia Wulandari; Vip Paramarta (PT. INOVASI TEKNOLOGI KOMPUTER, 2025)
Hospitals as health service providers have an important role in ensuring that people get optimal care. Factors that influence a person's decision to choose a hospital include service quality, hospital image, patient trust, and the effectiveness of Corporate Social Responsibility (CSR) programs. This study aims to analyze the effect of CSR implementation, hospital image, and patient trust on patient decisions in choosing a hospital. The method used in this study is a systematic literature review by collecting and analyzing 9 relevant articles from various databases. The results of the study indicate that CSR programs in the health sector have a positive impact on improving community welfare, a positive hospital image can increase patient trust, and patient trust in hospitals and medical personnel is a key factor in patients' decisions to seek treatment. This study provides important insights for hospital managers to develop more effective strategies in increasing the attractiveness of health services and strengthening relationships with the community